Spectra of Bochner-Riesz Means on Lp. (2nd October 2016) - Chen, Yang; Fang, Qiquan; Sun, Qiyu
ABSTRACT: In this article, the Bochner-Riesz means are shown to have either the unit interval [0, 1] or the whole complex plane as their spectra on L p, 1≤ p < ∞ .